Effect of Flash Drying on the Physicochemical Characteristics of Tapioca Starch - Nasution, Januar; Widodo, Felix; Lo, Diana; Phothisoot, Thitipong; Kongpichitchoke, Teeradate (Journal of Applied Agricultural Science and Technology, 2024)
Tapioca starch is widely used as a relatively cheap binder, thickener, and emulsion stabilizer. The product is often produced in Indonesia through several drying methods capable of influencing the functional properties and commercial price. Therefore, this study aimed to compare the effect of flash and sun drying on the physicochemical properties of tapioca starch. The focus was on the viscosity, change time from starch to dough, solubility level, gelatinization time, final gelatin height, color, white level, moisture content, degree of acid, crude fiber, and starch percentage. The results showed that flash drying significantly reduced the viscosity, a* value, white level, moisture content, and degree of acid. Meanwhile, the change time from starch to dough and L* value was significantly higher. It was concluded that flash drying had several advantages and disadvantages over sun-drying but could be used as an alternative time-efficient and more hygienic method.